Improving LSB Steganography using Filtering approach along with AES and RSTEG - P I, Sumayya; K, Sheena Kurian (IJRDO -Journal of Computer Science Engineering, 2015)
In steganography, sending a secret message securely through the network is done by hiding the message in a cover media. Variant techniques are available for steganography according to the specific needs and the world is competing to develop much efficient techniques than the present methods. A new way of securing the data is proposed here which makes use of the combination of two data securing techniques. The technique improves the security, as the message is not directly embedded in the cover image, instead a filtering based approach is done. Accordingly a status is provided in the LSB of the pixel, which helps in retrieving the hidden message. The proposed method uses the MSB bits of pixels for decision making. Multilevel steganography is done by incorporating retransmission steganography. The embedded message is encrypted before embedding which improves the security level. It is effortful for a snooper to retrieve the actual message as it is very different from the common LSB method. It is being found out that the proposed method hides large data in a single image retaining the advantages and discarding the disadvantages of the traditional LSB method. The Mean Square Error (MSE) and Peak Signal-to-Noise Ratio (PSNR) and the histogram differences can be used to measure the image quality and efficiency of the technique.